Degradable and Excretable Ultrasmall Transition Metal Selenide Nanodots for High‐Performance Computed Tomography Bioimaging‐Guided Photonic Tumor Nanomedicine in NIR‐II Biowindow. (21st January 2021) - Dong, Lile; Sun, Lining; Li, Wenjuan; Jiang, Yunping; Zhan, Yingying; Yu, Luodan; Chen, Yu; Hong, Guobin
Abstract: Transition metal selenide nanodots (NDs) represent distinctive antitumor agents for cancer treatment, but their non‐biodegradability may bring serious adverse effects and potential long‐term toxicity to internal tissues/organs, which substantially hinder their further clinical translations. In this work, the construction of a multifunctional theranostic nanosystem based on degradable and excretable ultrasmall Rh3 Se8 NDs by a general bovine serum albumin‐templated strategy is reported. The constructed Rh3 Se8 NDs exhibit distinctively high photothermal‐conversion efficiency (57.5%) in the second near‐infrared biowindow, making them highly applicable for photoacoustic imaging and photonic hyperthermia at the desired wavelength. Rh3 Se8 NDs exhibit a high tumor growth inhibition rate (98.1%) on 4T1 breast tumor‐bearing mice due to the desirable photonic hyperthermia performances. Especially, the fabricated Rh3 Se8 NDs feature the large X‐ray attenuation coefficients of the Rh component for contrast‐enhanced X‐ray computed tomography imaging. Importantly, the prominent biodegradability of Rh3 Se8 NDs enables their quick excretion out of the body for potentially avoiding inflammation and mitigating long‐term toxicity. Therefore, this work highlights the construction of proof‐of‐concept biodegradable and excretable ultrasmall inorganic theranostic nanosystems for multiple bioimaging‐guided cancer nanotherapeutics, guaranteeing the further clinical translations of inorganic nanoparticles in biomedicine. Abstract : Biodegradable and excretable ultrasmall Rh3 Se8 nanodots as a desirable theranostic nanosystem are designed and constructed for high‐performance computed tomography bioimaging‐guided photonic tumor nanomedicine in the second biological window (NIR‐II). These Rh3 Se8 NDs feature fast degradability, easy excretion, and high photothermal‐conversion efficiency (57.5%) in the NIR‐II biowindow, which is systematically demonstrated at the intracellular level and on animal xenografts.